Indicador de qualidade de vida do trabalhador florestal – “IQVTfor” - Lazarotto, Samara (2025)
Worker quality of life has become an increasing and important concern, especially in labor-intensive sectors such as forestry. Studies show that job satisfaction directly influences workers' well-being, impacting both productivity and organizational sustainability. In Brazil, where the forestry sector generates over one million jobs, assessing the quality of life of these professionals is essential to improving working conditions and enhancing industry efficiency. To address this need, this study aimed to develop and validate the Forestry Worker Quality of Life Index (IQVTfor), an instrument designed to measure subjective aspects such as worker satisfaction and well-being. The methodology included a systematic literature review on quality of work life and measurement methodologies. After that, a structured questionnaire was created and adapted to the reality of forestry workers, then applied within a forestry-based company. The collected data were analyzed using descriptive statistics and reliability tests, including Cronbach’s Alpha, ensuring the robustness and accuracy of the instrument. The results confirmed that IQVTfor is a valid and reliable tool for quantifying factors such as working conditions, well-being, and job satisfaction. The analysis also revealed that different dimensions of quality of life affect employees in distinct ways. In conclusion, IQVTfor proves to be an effective tool for forestry companies seeking to improve their work environment. In addition to providing a precise diagnosis, the index enables continuous monitoring of workers’ quality of life, aligning with sustainability and organizational well-being guidelines. Its implementation can significantly contribute to the appreciation and recognition of labor in the forestry sector.